Lattice preferred orientation of graphite determined by the anisotropy of out-of-phase magnetic susceptibility. (January 2022) - Hrouda, František; Franěk, Jan; Gilder, Stuart; Chadima, Martin; Ježek, Josef; Mrázová, Štěpánka; Poňavič, Michal; Racek, Martin
Abstract: Single crystals of graphite are diamagnetic with a strong crystalline anisotropy. Their magnetic susceptibility measured in alternating fields exhibits a weak, negative in-phase component and a relatively strong out-of-phase component due to electric eddy currents. Consequently, if graphite crystals are oriented preferentially by their crystal lattices (LPO) in graphite ore, one would expect a strong anisotropy of magnetic susceptibility (AMS) of the bulk rock. However, the standard AMS, which is the anisotropy of the in-phase component of susceptibility (ipAMS), reflects not only the LPO of graphite, but also the preferred orientation of the paramagnetic and ferromagnetic admixtures. On the other hand, the anisotropy of out-of-phase susceptibility (opAMS) in rocks such as these should directly indicate the graphite LPO due to its strong electrical conductivity, and can therefore be considered free from the contributions of non-conductive paramagnetic and ferromagnetic minerals. These competing factors were tested on natural metamorphic graphite ores near the South Bohemian town of Český Krumlov in the Moldanubian Zone. The ipMS of the ore is very low, 10 −6 to 10 −4 [SI], being positive in some specimens and negative in others, which indicates mixtures with variable proportions of graphite and paramagnetic-ferromagnetic minerals. On the other hand, opMS is exclusively positive, on the order of 10 −5 to 10 −4, and is strongly indicative of graphite. The degree of opAMS is distinctly high at 200–300%, and the opAMS lineation is closely perpendicular to the metamorphic foliation in ores and wall rocks. All this indicates a conspicuous LPO of graphite in the ore that was probably created during Variscan regional metamorphism and associated ductile deformation. Highlights: Anisotropy of out-of-phase magnetic susceptibility of graphite-bearing rocks and ores. Origin of magnetic fabrics. Preferred orientation of graphite by crystal lattice using magnetic methods. Good correlation of preferred orientation of graphite determined magnetically and non-magnetically.